2017
DOI: 10.1038/onc.2017.263
|View full text |Cite
|
Sign up to set email alerts
|

Role of HSPA1L as a cellular prion protein stabilizer in tumor progression via HIF-1α/GP78 axis

Abstract: The cellular prion protein (PrP) is associated with metastasis, tumor progression and recurrence; however, the precise mechanisms underlying its action is not well understood. Our study found that PrP degradation decreased tumor progression in colorectal cancer (CRC). In a CRC cell line and human CRC tissue exposed to hypoxia, induced heat-shock 70-kDa protein-1-like (HSPA1L) expression stabilized hypoxia-inducible factor-1α (HIF-1α) protein and promoted PrP accumulation and tumorigenicity in vivo. PrP was deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 61 publications
6
39
0
Order By: Relevance
“…Nevertheless, the correlation between PrP C and cancer stem cells remains to be determined. Our previous study has shown that high PrP C expression in colorectal cancer patients was significantly associated with metastasis risk, advanced clinical stages, and patient survival . We identified the correlation between PrP C and colon cancer stem cells by confirming the association between PrP C and Oct4.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, the correlation between PrP C and cancer stem cells remains to be determined. Our previous study has shown that high PrP C expression in colorectal cancer patients was significantly associated with metastasis risk, advanced clinical stages, and patient survival . We identified the correlation between PrP C and colon cancer stem cells by confirming the association between PrP C and Oct4.…”
Section: Discussionsupporting
confidence: 73%
“…PrP C and HSP70‐HSP90‐organizing protein are associated with glioblastoma proliferation and low patient survival rates . Our previous study has shown that HSPA1L stabilizes cellular prion protein . PRNP overexpression increased HSPA1L expression.…”
Section: Discussionmentioning
confidence: 94%
“…This study has verified that melatonin-induced mitophagy in Lee, Han, Yoon, et al, 2017;Lee et al, 2018;Mayer & Bukau, 2005;Wang et al, 2013). In damaged mitochondria of HeLa cells, HSPA1L and BAG family molecular chaperone regulator 4 induces the translocation of parkin to mitochondria, leading to mitochondrial quality control (Hasson et al, 2013).…”
Section: Discussionsupporting
confidence: 59%
“…This study has verified that melatonin‐induced mitophagy in senescent MSCs is regulated by the recruitment of the HSPA1L‐PrP C complex. HSPA1L contributes to protein stabilization, cell growth, apoptosis, and signal transduction (Hasson et al, ; Lee, Han, Yoon, et al, ; Lee et al, ; Mayer & Bukau, ; Wang et al, ). In damaged mitochondria of HeLa cells, HSPA1L and BAG family molecular chaperone regulator 4 induces the translocation of parkin to mitochondria, leading to mitochondrial quality control (Hasson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate how miR‐4516 regulates the expression of PrP C , the level of GP78 was assessed via expression of miR‐4516. Our previous study has shown that the level of PrP C is regulated by GP78 which is an membrane‐anchored E3 ligase . Inhibition of miR‐4516 significantly increased the expression of GP78, resulting in augmentation of ubiquitination of PrP C (Figure A‐D).…”
Section: Resultsmentioning
confidence: 86%